GAMBARAN TEKANAN DARAH PADA PEKERJA PENGELOLAAN MINYAK BUMI DI PT. PERTAMINA PLAJU ILIR TAHUN 2019 - Maria Ulfa; Amalia (Stikes Bina Husada, 2021)
National prevalence of people with high blood pressure is 30.9%. The prevalence of high blood pressure in women (32.9%) is higher than in men (28.7%). The prevalence in urban areas is slightly higher (31.7%) compared to rural areas (30.2%). Based on the results of an initial survey conducted at PT Pertamina Plaju Ilir in 2017, a total of 875, and in 2018 a total of 801 were in the RU III field site. The results of the survey and initial interviews with 5 residents said that they had caused complications of blood pressure disorders. Therefore, hypertension needs to be detected early, namely by checking blood pressure regularly.This study aims to know the description of blood pressure in oil processing workers at PT. Pertamina Plaju Ilir Year 2019. The design of this research is quantitative with cross sectional approach. The population of this study was all RU III workers, totaling 801 workers. The sample of this study was 86 sampling techniques using accindental sampling. The research instrument used a questionnaire. Bivariate analysis used chi square test with significance level (? = 0.05). This research was conducted on July 1 to 7, 2019.The results of this study indicate that there is a relationship between age (p = 0.008), gender (p = 0.041), physical activity (p = 0.014), exposure to cigarette smoke (p = 0.042) with blood pressure disorders in workers at PT Pertamina Plaju Ilir Palembang in 2019. The conclusion of this study is the relationship of age, sex, physical activity and exposure to cigarette smoke with blood pressure disorders in workers. It is recommended for employees to exercise a lot of sports, not smoking in the area of ??the oil refinery location and for PT Pertamina Plaju Palembang to increase counseling and socialization in the form of leafleats or banners on matters relating to health issues in the prevention of hypertension.